2020
DOI: 10.1103/physrevb.102.155423
|View full text |Cite
|
Sign up to set email alerts
|

Internal geometric friction in a Kitaev-chain heat engine

Abstract: We investigate a heat engine with a finite-length Kitaev chain in an ideal Otto cycle. It is found that the critical point of the topological phase transition coincides with the maxima of the efficiency and work output of the total Otto engine. Finite-size effects are taken into account using the method of Hill's nanothermodynamics, as well as using the method of temperature-dependent energy levels. We identify the bulk and boundary thermal cycles of the Kitaev chain engine and find that they are nonideal Otto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…The behavior of Ω is a multiparticle property and, as such, may exihibit the interference of different frequencies. Studying these phases from the perspective of quantum heat engines and temperature dependent energy levels [68] may also lead to new and interesting heat phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of Ω is a multiparticle property and, as such, may exihibit the interference of different frequencies. Studying these phases from the perspective of quantum heat engines and temperature dependent energy levels [68] may also lead to new and interesting heat phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Different platforms have been used to study such machines, for example, Rydberg atoms [115], multiferroic chain [116], etc. Such WMs allow us to study quantum thermal machines in presence of several many-body effects, including topological phase transitions [60,117,118], superfluid to insulating phase transition [63] and time-translation symmetry breaking [119], to name a few. Here we discuss a few such quantum engines studied recently, to highlight the non-trivial role played by inter-particle interactions in the operation of quantum machines.…”
Section: Interacting Many-body Quantum Thermal Machinesmentioning
confidence: 99%
“…Recently, effects of topological phase transitions on the performance of quantum heat engines have been studied [60]. In particular, studies on Otto heat engine with a finite length Kitaev chain as the working medium has shown that topological phase transition can enhance the efficiency, as well as work output of such engines [117].…”
Section: Unitary Strokementioning
confidence: 99%
“…A formalism based on the Hill nanothermodynamics [65], which is specially suited to analyze thermodynamics of finite size systems [66][67][68][69][70][71][72], gives a very interesting perspective on topological phase transitions [73][74][75][76][77][78], despite the intrinsically nonextensive character of topological systems. Due to the bulk-boundary correspondence, the transition at the bulk is related to the one at the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…As these components have different dimensions, they usually display phase transitions with different orders [73][74][75][76][77]. The nanothermodynamics approach is very robust, being able to describe systems without bulk-boundary correspondence [76], higherorder topological insulators [77] and even heat machines [78].…”
Section: Introductionmentioning
confidence: 99%